Estimation of supply and demand for public health nurses in Japan: A stock-flow approach - Kazuya Taira; Masanao Horikawa; Takahiro Itaya; Rikuya Hosokawa; Misa Shiomi (PLoS ONE, 2025)
Public health nurses (PHNs) play a central role in community health in Japan, and the number of certified PHNs has decreased since 2011. However, thus far, no study has estimated the supply and demand of PHNs in the coming years. The present study aimed to estimate the future balance between supply and demand for PHNs in Japan. This simulation study adopted a stock-flow approach using data from a survey of local governments, log data from a recruitment information website, and government statistics. The supply was estimated by adding up the numbers of newly hired PHNs and job changers to that of PHNs from the human resource pool. The demand was estimated from the number of PHNs needed in the future calculated by demographics assumed to affect the demand for PHNs. At the current job change rate to PHNs, the gaps between future supply and demand of PHNs were expected to be −494 to −50 in 2025, −1,007 to −435 in 2030, and −772 to −330 in 2035. If the job change rate would be 1.5 times, the gaps were estimated to be 285 to 729 in 2025, −431 to 141 in 2030, and −182 to 260 in 2035. If the job change rate would be 2.0 times, the supply was sufficient for all estimated years. The number of PHNs working in Japanese local governments is estimated to decline until 2035, resulting in a shortage. Policy makers should consider early measures to adjust the future number of PHNs.